Loan Loss Provisioning Behaviour- An Empirical study of Indian Banks - Famila, Maria Theresa (2016)
This paper aims to model the determinants of Loan Losses Provisions (LLP) behaviour in Indian banks as a function of certain bank specific and macroeconomic variables. The study covering an unbalanced data of Indian banks over a period of 8 years (from 2008 to 2015) post Global Financial Crisis, examines the relationship of LLP with income smoothing, capital management, X-efficiency, Z-score and certain macro-economic variables. The study concludes that LLP is affected by more than one factor, namely X-efficiency and Z-score and also by macro economic variables such as Unemployment and Money Growth. While Z-score (bank stability) was negatively correlated with LLP as expected, X-efficiency exhibited positive relationship with LLP indicating discretionary provisioning by bank managements, which was as a countercyclical measure rather than as income smoothing. The macro variable influences were also in support of this conclusion.